Modelling of pilot-scale anaerobic food wastes composting process with dry leaves or cow manure - Lim, Wei Jie; Chin, Nyuk Ling; Yusof, Yus Aniza; Yahya, Azmi; Tee, Tuan Poy (Universiti Putra Malaysia Press, 2019)
Anaerobic composting is a promising method to fully transform food wastes into useful materials such as biofertilizer and biogas. In this study, the optimum proportions of food wastes containing vegetable, fruit and meat wastes with dry leaves or cow manure for composting were determined using the simplex centroid design and response optimizer. The effectiveness of the pilot-scale composting process was evaluated based on the targeted compost quality of C/N ratio at 21, pH value at 8 and electrical conductivity of 1 dS/m. Food wastes composting formulation with dry leaves suggested high percentage of dry leaves, 86.9% with low food wastes composition of 13.1% constituted by vegetable waste (1.1%), fruit waste (4.9%) and meat waste (7.1%). With cow manure formulation, only 6% of cow manure was recommended with another 94.0% of food wastes contributed by a fair mix of vegetable waste (23.2%), fruit waste (34.3%) and meat waste (36.5%). The developed regression models were experimentally validated with predicted responses obtained in acceptable ranges for C/N ratio (21.2 - 21.8), pH (7.92 - 7.99) and electrical conductivity (0.97 - 1.03 dS/m).